2015
DOI: 10.5194/os-11-719-2015
|View full text |Cite
|
Sign up to set email alerts
|

Global representation of tropical cyclone-induced short-term ocean thermal changes using Argo data

Abstract: Abstract. Argo floats are used to examine tropical cyclone (TC) induced ocean thermal changes on the global scale by comparing temperature profiles before and after TC passage. We present a footprint method that analyzes cross-track thermal responses along all storm tracks during the period 2004-2012. We combine the results into composite representations of the vertical structure of the average thermal response for two different categories: tropical storms/tropical depressions (TS/TD) and hurricanes. The two f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
58
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 59 publications
(96 reference statements)
10
58
0
Order By: Relevance
“…Although the air‐sea flux can be as large as 260 MJ/m 2 at certain small location for a category 5 typhoon [ Shay et al ., ], the typical value of air‐sea flux was quite smaller, e.g., area average value of the whole forcing region is only about 20–30 MJ/m 2 [ Shay et al ., ] and 40 MJ/m 2 for a category 2 typhoon [ Sun et al ., ]. The annual mean of air‐sea flux due to typhoon forcing on the global scale is 34 MJ/m 2 (11.05 w/m 2 ) [ Cheng et al ., ]. It implies that such huge subsurface heat content loss in the AEs cannot be simply due to the local air‐sea interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the air‐sea flux can be as large as 260 MJ/m 2 at certain small location for a category 5 typhoon [ Shay et al ., ], the typical value of air‐sea flux was quite smaller, e.g., area average value of the whole forcing region is only about 20–30 MJ/m 2 [ Shay et al ., ] and 40 MJ/m 2 for a category 2 typhoon [ Sun et al ., ]. The annual mean of air‐sea flux due to typhoon forcing on the global scale is 34 MJ/m 2 (11.05 w/m 2 ) [ Cheng et al ., ]. It implies that such huge subsurface heat content loss in the AEs cannot be simply due to the local air‐sea interaction.…”
Section: Resultsmentioning
confidence: 99%
“…The only difference is that the maximum cooling occurred at 350 m in the CEs, whereas the maximum cooling occurred at subsurface of 100 m depth in the AEs. Previous study also identified the cooling center at 100 and 350 m depth [ Cheng et al ., ]. In this study, only two different cooling centers are detected in the CEs and AEs.…”
Section: Resultsmentioning
confidence: 99%
“…We analyze SST responses for storm days with weak intensity (Categories 1 and 2) and medium to high intensity (Categories 3–5). The temporal evolution of the SST cooling is consistent among all three models, and the magnitude of cooling is within the range of observation‐based estimates [ D'Asaro et al ., , ; Cheng et al ., ] and other modeling studies [ Vincent et al ., ; Li et al ., ; Jullien et al ., ]. The anomalous cooling before the storm arrival (Day 0 in Figure ) is likely due to the cold wakes left by the earlier storms.…”
Section: Resultsmentioning
confidence: 99%
“…The figure reveals that a persistent cooling below the thermocline warming that acts to compensate the OHU. This deep cooling is also found in other observation‐based and modeling studies [ Cheng et al ., ; Jullien et al ., ]. The cooling occurs mainly in the Southern Indian ocean near the Seychelles‐Chagos thermocline ridge (5°S–15°S) (see supporting information animations and Figures S4 and S5), where the shallow thermocline permits efficient vertical mixing and strong upwelling of cold water by TC‐induced Ekman pumping.…”
Section: Resultsmentioning
confidence: 99%
“…Ocean‐atmosphere coupling is also important for analyzing TC‐induced feedbacks that can influence climate variability. An increasing number of studies have found TC‐induced ocean vertical mixing can lead to ocean heat uptake and transport (Bueti et al, ; Cheng et al, ; Emanuel, ; Jansen et al, ; Jullien et al, ; Li & Sriver, ; Sriver & Huber, ), potentially influencing global SST patterns and affecting large‐scale circulations in the ocean and the atmosphere (Fedorov et al, ; Sriver & Huber, ). These potential feedbacks can affect climate mean‐state and variability on seasonal to interannual time scales.…”
Section: Introductionmentioning
confidence: 99%